2019
DOI: 10.1128/aem.03058-18
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Analogs of Plant Tetrahydropyridine Alkaloids Mediate Microbial Interactions in a Rhizosphere Model System

Abstract: Plants expend significant resources to select and maintain rhizosphere communities that benefit their growth and protect them from pathogens. A better understanding of assembly and function of rhizosphere microbial communities will provide new avenues for improving crop production. Secretion of antibiotics is one means by which bacteria interact with neighboring microbes and sometimes change community composition. In our analysis of a taxonomically diverse consortium from the soybean rhizosphere, we found that… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 33 publications
2
34
0
Order By: Relevance
“…Primary genome assembly generated 40 contigs with 59.8% GC content and a scaffold N50 value of 438,962 bp. Similar reports of genome assembly of P. koreensis strains from soybean and rice rhizosphere have been published earlier (Lozano et al 2019;Lin et al 2016). In this study, genome validation and quality control using Bowtie software revealed 29 million reads mapped concordantly and 6 million reads mapped discordantly with an overall alignment rate of 97.82%.…”
Section: Resultssupporting
confidence: 85%
“…Primary genome assembly generated 40 contigs with 59.8% GC content and a scaffold N50 value of 438,962 bp. Similar reports of genome assembly of P. koreensis strains from soybean and rice rhizosphere have been published earlier (Lozano et al 2019;Lin et al 2016). In this study, genome validation and quality control using Bowtie software revealed 29 million reads mapped concordantly and 6 million reads mapped discordantly with an overall alignment rate of 97.82%.…”
Section: Resultssupporting
confidence: 85%
“…They have a wide range of biological activities, including insecticidal [55], antibacterial and antifungal [56][57][58]. Literature does mention other alkaloid compounds produced by P. fluorescens, such as pyrrolnitrin or hydropyridine-type compounds that also show antibiotic and antifungal activity [28,59]. However, hapalindole-type natural products have never been described in P. fluorescens; hence, this result would require further investigation to be more conclusive.…”
Section: Discussionmentioning
confidence: 99%
“…Model communities could, for example, be used to elucidate how microorganisms share metabolites and partition resources [20] , [21] , [22] , under what conditions communities are dominated by competitive or cooperative interactions [23] , [24] , [25] , which specific genes that govern community interactions through e.g. secondary metabolites [26] , [27] , and to what extent interactions are dependent on environmental changes [28] . Furthermore, model systems can aid in understanding the links between taxonomic and functional diversity [29] , what factors that contributes to community stability in the face of invasion from non-resident strains or other stressors [30] , [31] , highlight important keystone species for functional stability of a community [32] , [33] , and shed light on the evolution of mutualism between microbes [34] , [35] .…”
Section: What Constitutes a Good Microbial Community Model?mentioning
confidence: 99%
“…That said, they comprise completely non-overlapping sets of members; SXMP consists of Stenotrophomonas rhizophila , Xanthomonas retroflexus , Microbacterium oxydans and Paenibacillus amylolyticus , while THOR is built on Pseudomonas koreensis , Flavobacterium johnsoniae and Bacillus cereus . Arguably, the members of THOR would be easier to genetically manipulate using standard protocols, but that has not prevented the SXMP community to be used in a variety of studies [30] , [42] , [62] , [63] , [64] , [65] , compared to THOR which was more recently introduced as a model [26] , [52] . The ease of genetic manipulation and the many known interactions between the species in these model communities make them ideal for identifying which genes that are responsible for interaction behaviors between microbial species.…”
Section: Community Models – From Simple To Complexmentioning
confidence: 99%
See 1 more Smart Citation